S126 Is there golden hour of non invasive ventilation (NIV) treatment in patients with acute hypercapnic respiratory failure (AHRF)?. (December 2018) - Edwards, L; Pressler, N; Pandit, D; Pagaria, M
Abstract : Introduction: Identifying the predictors of NIV failure has attracted significant interest because of the strong link between failure and poor outcomes. Previous studies have shown a poor correlation between admission pH and pCO2 to mortality. This study was aimed to identify if improvement after the first hour of NIV treatment could predict mortality in this group of patients with AHRF. Methods: Retrospective analysis of data for patients requiring NIV over a 5 year period. Patients were included in the samples who received NIV for COPD and non-COPD causes of AHRF. Results: A total of 187 cases were analysed in the period. Out of these 187 cases, 141 survived to discharge and 46 died during their inpatient stay. The mean pre-NIV pH in the deceased group was 7.09 compared to 7.23 in the survival group. The mean one-hour post NIV pH in the deceased group was 7.17 compared to 7.34 in the survival group. There was no statistically significant difference in the pH of the two groups prior to NIV, however the difference in pH was statistically significant between the two groups following 1 hour of NIV treatment (p=0.03). There was no statistically significant difference in the pCO2 between the groups before or after NIV treatment, nor a difference in the pCO2 reduction. Conclusion: These results show that both groups had an improvement in their pH following 1 hour of NIV, but there was a statistically significant difference in the pH of patients who survived compared to those who did not. The CO2 improvement was actually higher in the patients who died, therefore rate of CO2 reduction cannot be used to predict mortality, and the pH difference between these patients is not due to better CO2 clearance. These results show that there is not a 'Golden Hour' of NIV management whereby improving respiratory acidosis quickly decreases mortality. However it does demonstrate the well advertised 'Golden Hour' of initial patient management whereby improving overall acidosis can reduce mortality. In unwell patients with AHRF simultaneous treatment of sepsis/AKI with antibiotic/fluids is equally as important.